Development of a Learning Module on Linear Motion Material Using Robotics Based on Miniature Sahur Arakan Integrated with a STEM Approach - M. Arif Rahman Hakim; Haerul Pathoni; Syamsurizal (Mataram University, 2026)
The integration of local wisdom in physics learning remains limited, and no module simultaneously combining the Arakan Sahur tradition, robotics technology, and the STEM approach has yet been developed. This study aimed to develop a straight-motion learning module using robotics based on Arakan Sahur miniatures integrated with STEM and to analyze its feasibility in terms of content quality, presentation, usability, and implementation in learning activities. The study employed the Research and Development (R&D) method using the Borg and Gall model limited to five stages. Data were collected through material expert validation questionnaires, media expert validation questionnaires, teacher perception questionnaires, student response questionnaires, and interviews. The feasibility indicators included material relevance, language clarity, content presentation, STEM integration, self-instructional characteristics, stand-alone usability, and user-friendliness of the module. The results showed that material expert validation achieved an average score of 3.47 (very good), while media expert validation reached 3.50 (very good) after two rounds of revision. Teacher perceptions obtained an average score of 3.44 (very good), and responses from 22 students reached 3.55 (very good). The module also demonstrated explicit implementation of the four STEM components through robotics programming, motion analysis, engineering design, and mathematical calculations. In addition, 95.5% of students showed high interest in learning physics using robotics-based activities. In conclusion, the developed module is considered valid and practical for use in high school physics learning and contributes as an innovative teaching material integrating physics concepts, local culture, robotics, and STEM learning.